Text on back: 'Eröffnung der Reichskonferenz in Berlin. Ledebour verlässt das Reichskanzler-Palais' - Sennecke, Robert,
Text on back: 'Eröffnung der Reichskonferenz in Berlin. Ledebour verlässt das Reichskanzler-Palais'.